Modulating Workload for Air Traffic Controllers during Airport Ground Operations. (September 2015) - Chua, Zarrin; Causse, Mickaël; Cousy, Mathieu; Andre, Fabien
Evaluating future technology concepts for air traffic control ground operations requires exploration of work scenarios of differing complexities, i.e. scenarios that create more or less taskload for air traffic controllers. While the link between traffic load and workload has been well-characterized in the literature and is often the only complexity variable applied to validation studies, there are other operational events that can augment controller workload. Through a series of interviews and on-site observations of professional and student air traffic controllers, we defined seven general operational events that can be applied to all airport ground operations. We discuss the development of two scenarios of different workloads (average and hard) and their validation with air traffic controllers.